Structural Redundancy Assessment of Adjacent Precast Concrete Box-Beam Bridges in Service - Yanling Leng; Jinquan Zhang; Ruinian Jiang; Yangjian Xiao (Advances in Materials Science and Engineering)
Present approaches for assessing bridge redundancy are mainly based on nonlinear finite element (FE) analysis. Unfortunately, the real behavior of bridges in the nonlinear range is difficult to evaluate and a sound basis for the nonlinear FE analysis is not available. In addition, a nonlinear FE analysis is not feasible for practitioners to use. To tackle this problem, a new simplified approach based on linear FE analysis and field load testing is introduced in this paper to address the particular structural feature and topology of adjacent precast concrete box-beam bridges for the assessment of structural redundancy. The approach was first experimentally analyzed on a model bridge and then validated by a case study. The approach agrees well with the existing recognized method while reducing the computation complexity and improving the reliability. The analysis reveals that the level of redundancy of the bridge in the case study does not meet the recommended standard, indicating that the system factor recommended by the current bridge evaluation code for this bridge is inappropriate if considering the field condition. Further research on the redundancy level of this type of bridges is consequently recommended.